ANALISIS PENGUKURAN KINERJA DENGAN MENGGUNAKAN KONSEP VALUE FOR MONEY PADA PEMERINTAH DAERAH (Studi pada Pemerintah Kabupaten/Kota di Provinsi Banten Periode 2015-2019) - Anwar, Ilma Fauziah (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2022)
This study aims to determine the analysis of local government performance measurement using the concept of Value For Money. This method is a concept of measuring the performance of the public sector based on three elements, namely economic, efficiency, and effectiveness. The types of data used in this study are qualitative and quantitative data. The data source used is secondary data. The sample in this study amounted to 9 District / City Government Financial Reports (LKPD) in Banten Province during 2015-2019. Sampling in this study using purposive sampling by selecting the APBD and the APBD Realization Report. The results of the data analysis show that the performance of the district / city governments in Banten Province using the concept of Value For Money. In general, there are only a few areas that have met the level of economic ratios, efficiency and effectiveness, namely Kota Serang, Kota Tanggerang and Kota Tanggerang Selatan. Keywords: Value For Money, Economic, Efficiency, Effectiveness